The Effect of Word Wall Strategy on Students’ Vocabulary Achievement at SMP Negeri 5 Pematangsiantar in the Academic Year 2018/2019 - Rohdearni Wati Sipayung (Budapest International Research and Critics University, 2018)
English is an international language. This research is aimed to improve students’ vocabulary achievement in antonym of adjective to the seventh grade of SMP Negeri 5 Pematangsiantar in academic year 2018/2019. The material which will be tested is vocabulary in antonym of adjective. This study was an action research study. Statement of the problem of this research is “how is the students’ vocabulary achievement improved by using word wall strategy?” The objective in this research is to know the students’ vocabulary achievement by using word wall strategy. The samples of this research were 32 students of VII-3 class. The data were form of quantitative data. The quantitative data were collected from giving them test (matching test) to see the improvement of the students’ vocabulary achievement by score of pre-test and post-test. The result of the students’ progress during the teaching learning process by using word wall strategy was good. The students’ achievement increased from giving them pre-test and post-test. It could be seen the average of the score of pre-test and post-test, the result of pre-test was 42, 58 while post-test was 91, 61. The different of the score was significant. It means that using Word Wall strategy in teaching can improve the students’ vocabulary achievement. Finally the researcher suggests using this strategy in teaching learning process especially in teaching vocabulary.